The Process of Acquiring Declarative Sentence on Aphasia - Muzakky, Muhammad; Fahriany, Fahriany; Utami, Meli Aulia (Lingual Journal of Language and Culture, 2021)
The present study investigates the process of acquiring declarative sentences in aphasia language learners. This study seeks to address the question of how the process of an aphasia language learner to acquire declarative sentences. Using a case study, the process of interview was implemented to explore the subject's response toward this issue. The subject is an adult language learner who is 69 years old. The data were obtained from interviews and documents. The interview section was used to explore the process of acquiring declarative sentences, and the documents were used to check the validity of the interview. The data analysis of acquiring declarative sentences showed: (1) the process of acquiring the language on an adult is through behaviorist theory that consists of subject's routinizes in reading books, newspapers, and comics. (2) In adult language learners, the duration of acquiring the language is not too long and challenging. The subject takes a significant effort to deal with various activities, and it is the characteristic of an adult in acquiring the language. (3) In the construction of declarative sentences, the subjects could produce six sentences correctly and no grammar errors. He also could interact with others through those sentences. The challenge is on the way he produces, which is slowly mouth movement. Additionally, we open the gate of future research with pieces of evidence. It was recommended the future research on this study might be conducted in a quantitative method with more adult language learners involved.